A discussion of the control of nonferrous metallurgical processes∗. Issue 17 (2015) - Sun, Bei; Yang, Chunhua; Gui, Weihua
Abstract: Nonferrous metallurgical processes are featured by their complex nature. Control of nonferrous metallurgical processes is non-trivial and related to multiple disciplines. An example is presented to illustrate the basic procedure of nonferrous metallurgical process control. A feasible way to construct a unified control approach and the potential developments of nonferrous metallurgical process control are discussed.